ID: 101: ROTHIA MUCILAGINOSA BACTEREMIA: 8 YEAR REVIEW OF A SINGLE INSTITUTION EXPERIENCE. Issue 4 (22nd March 2016) - Abidi, M; Hari, P; Banerjee, A; Ledeboer, N
Abstract : Background: Rothia spp. are gram positive bacteria which are known to cause infections in the immune compromised host. Literature is limited on the epidemiology and clinical significance of Rothia bacteremia. Methods: We reviewed medical records of all patients with blood cultures positive from 2006–2014. Descriptive analysis was performed as well as comparative analysis of neutropenic patients (absolute neutrophil count ≤1000 /μL) at the time of bacteremia with non-neutropenic patients at the time of bacteremia. Fische's exact tests were used for comparisons of proportions and medians, respectively, with p-values <0.05 considered statistically significant. Results: 29 patients with Rothia bacteremia were identified. Median age was 58 years (range 27–73), with no significant gender difference (p=0.94). Charlson co-morbidity score of 4 or greater was found in 20 (69%) of patients; 20 (69%) patients had a hematologic malignancy or bone marrow transplant. While there were 14 deaths, only 1 was possibly attributed to Rothia infection. Neutropenia was observed in 21(72%) patients at the time of bacteremia. Neutropenic patients were less likely than non-neutropenic patients to have polymicrobial infection (24% vs. 63%, p=0.083); and were also more likely to have multiple positive blood cultures (76% vs. 0%; p value=0.0003). There was no difference between the two groups in need for ICU care, mortality or attributable mortality. Statistically significant difference was seen for steroid use (81% vs. 13%, p=0.0014), and fluroquinolone use (86% vs.13% p=<0.0001) preceding bacteremia in neutropenic patients. Presence of intra-vascular catheter was also more pre-dominant in the neutropenic group (86% vs. 50%, p=0.068) at the time of bacteremia. Conclusions: Rothia bacteremia is seen in patients with medical co-morbidities, predominantly in patients with leukemia. A significant association was seen with prior use of steroid and fluroquinolone prophylaxis in neutropenic patients who developed Rothia bacteremia. Rothia bacteremia in neutropenic hosts was mostly monomicrobial and less likely thought to be a contaminant.